Deep Drilled Shafts For The Pearl Harbor Memorial Bridge New Haven, Connecticut - Theodore von Rosenvinge (Deep Foundations Institute, 2011)
Large diameter (2.4 meter) drilled shaft foundations were installed to depths of over 62 meters through soil into Arkose bedrock for Connecticut?s Pearl Harbor Memorial Bridge (I-95 over New Haven Harbor). The project involved many ?firsts? including the first ?extradosed? cable-stayed bridge in the US, and for Connecticut, the deepest drilled shafts, the first use of a rotator to install shaft casing, and the first use of the Mini-Sid technology for rock socket bottom inspection. Design utilized both friction and end bearing for rock sockets. O-Cell testing was employed to maximize performance factors during design and to allow adjustments to socket lengths during construction. Favorable test results permitted a reduction in socket lengths and significant cost saving.